Conversion of cellulose to polyols over promoted nickel catalysts - Shrotri, Abhijit; Tanksale, Akshat; Beltramini, Jorge Norberto; Gurav, Hanmant; Chilukuri, Satyanarayana V. (Catalysis Science & Technology, 2012)
Sorbitol is one of the key platform chemicals that can be applied to several industrial applications, including bio-fuels and hydrogen production. Presently there is no commercial heterogeneous catalytic process to produce sorbitol from cellulose due to the low yield and high cost of noble metals required for the conversion. In this paper we describe an aqueous phase hydrolysis-hydrogenation process to convert cellulose to sorbitol using a cheap Ni based catalyst. Monometallic Ni catalysts showed little activity for the reaction, but with the addition of a small amount of Pt to the Ni catalyst (Ni : Pt = 22 : 1 atom ratio), the activity was greatly enhanced. Results showed that the bimetallic Ni-Pt catalysts supported on mesoporous alumina gave a hexitol (sorbitol + mannitol) yield of 32.4% compared to only 5% with a Ni catalyst. Moreover, Ni-Pt supported on a mesoporous beta zeolite support provided even higher yield of 36.6%. These results were obtained after only 6 hours of run at 200 degrees C and 50 bar H-2 pressure (at room temperature). The presence of a small amount of Pt promotes the protonation of water and hydrogen molecules, which spill over to Ni sites creating in situ acid sites to catalyse hydrolysis of cellulose.

Tuning the dimensionality of layered Srn+1Tin−xNixO3n+1 perovskite structures for improved activity in syngas generation - Dama, Srikanth (Journal of Catalysis, 2018)
Interest in perovskite type oxides is growing due to their versatile catalytic applications. A series of Ruddlesden-Popper (RP) type layered perovskite oxides Srn+1Tin−xNixO3n+1 were prepared and evaluated for their catalytic activity in steam reforming, CO2 reforming and bi-reforming of methane. These materials, prepared through citrate gel method were characterized to understand their structure and Ni reducibility. Substitution of Ni in RP phases was established through refinement of XRD powder pattern. During methane reforming, the catalytic activity increased with the order of RP phase of SrTi1−xNixO3−δ (n = ∞). TPR results show variation in Ni reducibility with the order of RP phase, while TPD-O2 study helped to estimate oxygen vacancies. These vacancies seem to influence catalytic activity during methane reforming. Transient pulse experiments show that CO2 dissociates over oxygen vacancies to give CO and oxygen, with later replenishing lattice oxygen in SrTi0.8Ni0.2O3−δ (n = ∞) phases. Highly labile oxygen vacancies generated in the bulk of SrTi0.8Ni0.2O3−δ must be migrating to the surface, helping in the removal of coke formed. Characterization of catalysts after reaction helped in better understanding of coke precursors.
Keywords: Dry reforming; NickelSyngas; Ruddlesden-Popper (RP) perovskites; Steam reforming